(untitled) (CIPEEX, 2025)
This paper examines the inadmissibility, in criminal proceedings, of evidence obtained by extracting data and private conversations from e-mail and social-network platforms (e.g., WhatsApp and Facebook) without prior judicial authorization, as well as the effects of the fruit-of-the-poisonous-tree doctrine on derivative evidence. It is a doctrinal and case-law review that systematizes the constitutional exclusionary rule (Federal Constitution, art. 5, LVI), the framework of the Brazilian Internet Bill of Rights, and higher-court decisions concerning the seizure of private messages by the police without judicial oversight. The aim is to set criteria for (in)admissibility of communicational data, to identify when illegality taints downstream evidence, and to point out limited distinctions—such as communications sent to corporate accounts functioning as work tools. The method consisted of critically analyzing scholarship and case law, with emphasis on chain of custody requirements and the need for a court order to access private communications. The findings show: (i) the exclusion of illegally obtained evidence and its fruits, subject to independent-source and inevitable-discovery exceptions; (ii) the nullity of evidence extracted from messaging apps absent a court order, with consequent suppression; and (iii) a distinction in precedents regarding messages sent to corporate e-mail or work tools, where no reasonable expectation of privacy was recognized. It concludes that respecting judicial warrant requirements and evidentiary chain of custody is a condition for valid digital evidence, and that the fruit-of-the-poisonous-tree doctrine safeguards procedural integrity and fundamental rights.